The Impact of Healthcare Expenditure and Healthcare Sector Growth on CO2 Emission using Dynamic Panel Data System GMM Estimation Model during COVID 19 Crisis - Samah, Irza Hanie Abu; Abd Rashid, Intan Maizura; Husain, Wan Ahmad Fauzi Wan; Ibrahim, Suraiya; Hamzah, Hariri; Amlus, Mohammad Harith (International Journal of Energy Economics and Policy, 2020)
As huge consumers of water and energy, healthcare sector have a significant environmental impact. The healthcare sector is accountable for answering countless the most dangerous effects of climate change and pollution, deadly environmental emissions and other greenhouse gases itself. This study aims to observe empirically the effect of healthcare expenditure and heath sectors growth on Co2 during Covid 19 outbreak in Malaysia. As the world has awakened to the potential risks of Covid 19, there has been a massive effort to add capacity to the healthcare system rapidly. In Malaysia, apart from stressing the need for the public to strictly adhere to the Movement Control Order (MCO), the government an immediate boost in funding for healthcare services through initial stage fiscal policy response to Covid 19 outbreak. This research used Dynamic Panel Data Model also known as longitudinal study. This study explained Dynamic Panel Data System GMM Estimation model is fitting to interpret the outcome, indicate healthcare expenditure and healthcare growth on Covid-19, inflation rate and unemployment rate have significant relationship with CO2 emission. Empirical findings suggest that CO2 emissions policies reforms are required to channelize healthcare sector growth to a more government spending resulting from fiscal policy designed by the government of Malaysia. The regulators of other countries should pull out CO2 emissions policies to achieve sustainable economic growth and health sector growth development. The results provide important information to allow comparisons of the health-care sector with other economic sectors in Malaysia and the global healthcare sector in terms of Co2 emission. In particular, the results are intended to contribute to the understanding of the Co2 emission of national healthcare systems so that policymakers, especially in low-income and middle-income countries, can develop relevant CO2 emissions mitigation policies. Keywords: Covid-19, Fiscal Policy, Healthcare expenditure, healthcare sector growth, CO2 emission, dynamic panel model, Malaysia. JEL Classifications: E31, Q41, Q57 DOI: https://doi.org/10.32479/ijeep.9769